Asynchronous Little Ice Age glacier fluctuations in Iceland and European Alps linked to shifts in subpolar North Atlantic circulation - Larsen, D.; Miller, Gifford; Geirsdottir, A. (Elsevier Science BV, 2013)
Records of past glacier fluctuations are an important source of paleoclimate data and provide context for future changes in global ice volume. In the North Atlantic region, glacier chronologies can be used to track the response of terrestrial environments to variations in marine conditions including circulation patterns and sea ice cover. However, the majority of glacier records are discontinuous and temporally restricted, owing in part to the extensive advance of Northern Hemisphere glaciers during the Little Ice Age (LIA), the most recent and severe climate anomaly of the Neoglacial period. Here, we combine an absolutely dated and continuous record of Langjökull ice marginal fluctuations with new reconstructions of sediment flux through the past 1.2 ka using varved sediments from Hvítárvatn, a proglacial lake in Iceland's central highlands. Large spatial and temporal variations in sediment flux related to changing ice cap dimensions are reconstructed from six sediment cores and seismic reflection profiles. Sediment data reveal two discrete phases of ice expansion occurring ca. 1400 to 1550 AD and ca. 1680 to 1890 AD. These advances are separated by a persistent interval of ice retreat, suggesting that a substantial period of warming interrupted LIA cold. The pattern of Icelandic glacier activity contrasts with that of European glaciers but shows strong similarities to reconstructed changes in North Atlantic oceanographic conditions, indicating differing regional responses to coupled ocean–atmosphere–sea ice variations. Our data suggest that subpolar North Atlantic circulation dynamics may have led to coherent asynchronous glacier fluctuations during the mid LIA and highlight the importance of circulation variability in triggering and transmitting multidecadal scale climate changes to nearby terrestrial environments.